Portfolio Assessment in the English Teaching Program at the UCR, Western Campus - Gamboa, Roy (Universidad de Costa Rica, Sede de Occidente, 2022)
Portfolios have been used as an assessment strategy for around four decades. Today, they continue to be relevant forms of assessment in different fields of education including EFL writing. Following a convergent mixed methods approach under the pragmatic worldview, this study investigated the extent to which portfolio assessment in the writing courses of the Bachelor’s in English Teaching (BET) program at UCR, West Campus brings into line theoretical principles of portfolio assessment. The data consisted of a set of six teacher-created portfolio guidelines which were analyzed using a theory-based checklist and the information collected via a teachers’ questionnaire that the six participant teachers in the study answered. Despite evidence of a high level of knowledge about theoretical principles of writing portfolio assessment on the part of the participant teachers, the results indicated a clear mismatch between such knowledge and the actual implementation of writing portfolios by the participants. Based on these results, it was suggested that participant teachers undergo specialized training on the implementation of writing portfolio assessment to assist them in closing the gap between writing portfolio assessment theory and their actual implementation in EFL writing courses of the BET program at UCR, West Campus.